2020
DOI: 10.1038/s41586-020-2223-y
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Mpro from SARS-CoV-2 and discovery of its inhibitors

Abstract: A new coronavirus (CoV) identified as COVID-19 virus is the etiological agent responsible for the 2019-2020 viral pneumonia outbreak that commenced in Wuhan [1][2][3][4] . Currently there are no targeted therapeutics and effective treatment options remain very limited. In order to rapidly discover lead compounds for clinical use, we initiated a program of combined structure-assisted drug design, virtual drug screening and high-throughput screening to identify new drug leads that target the COVID-19 virus main … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

126
4,702
2
63

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 3,787 publications
(4,893 citation statements)
references
References 43 publications
126
4,702
2
63
Order By: Relevance
“…The compounds identified in this study represent the most potent and selective hits reported so far, and are superior than recently reported SARS-CoV-2 M pro inhibitors ebselen, N3, and 13b (Table 5). Aside from the above positive results, we also showed that ritonavir (9) and lopinavir (10) failed to inhibit the SARS-CoV-2 M pro (IC50 > 20 µM, Fig. 2), which might explain their lack efficacy in clinical trials for COVID-19.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…The compounds identified in this study represent the most potent and selective hits reported so far, and are superior than recently reported SARS-CoV-2 M pro inhibitors ebselen, N3, and 13b (Table 5). Aside from the above positive results, we also showed that ritonavir (9) and lopinavir (10) failed to inhibit the SARS-CoV-2 M pro (IC50 > 20 µM, Fig. 2), which might explain their lack efficacy in clinical trials for COVID-19.…”
Section: Discussionmentioning
confidence: 74%
“…28 As the SARS-CoV-2 M pro shares a high sequence similarity with SARS and to a less extent with MERS, we reasoned that inhibiting the enzymatic activity of SARS-CoV-2 M pro will similarly prevent viral replication. 7,9 Noticeable findings from our study include: 1) Boceprevir (28) or aldehyde prodrug, the bisulfite (GC-376 (64)). This result suggests that reactive warheads might be essential for SARS-CoV-2 M pro inhibition.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations